TENZORDÍŃ FIZIKADA QOLLANÍLÍWÍ - Tanirbergenov, S.A.; Reymova, D.A. (SCIENCE and SOCIETY, 2024)
The article discusses in detail the application of tensors in physics. Here is information about the properties of the body’s inertia tensor and its components.